2022
DOI: 10.1186/s12950-022-00322-x
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluation of asthma–chronic obstructive pulmonary disease overlap using a mouse model of pulmonary disease

Abstract: Background Features of asthma and chronic obstructive pulmonary disease (COPD) can coexist in the same patient, in a condition termed asthma– chronic obstructive pulmonary disease overlap (ACO). ACO is heterogeneous condition exhibiting various combinations of asthma and COPD features. No clinically acceptable experimental model of ACO has been established. We aimed to establish an animal model of ACO. Methods We generated two phenotypes of ACO by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…SOD can effectively scavenge oxygen-free radicals and resist free radical damage. 25 In the present study, improvement of the above-mentioned indexes in the experimental group was significantly better than that in the conventional group after treatment, suggesting that the combination regimen could improve endothelial functioning of patients, regulate vascular tension, and effectively protect against serum lipid peroxidation injury, consistent with similar reports in the literature. [26][27][28] Meanwhile, regarding adverse reactions, this study observed no serious adverse reactions in patients treated with combination regimen, thereby demonstrating its potential clinical safety.…”
Section: Post-treatmentsupporting
confidence: 91%
“…SOD can effectively scavenge oxygen-free radicals and resist free radical damage. 25 In the present study, improvement of the above-mentioned indexes in the experimental group was significantly better than that in the conventional group after treatment, suggesting that the combination regimen could improve endothelial functioning of patients, regulate vascular tension, and effectively protect against serum lipid peroxidation injury, consistent with similar reports in the literature. [26][27][28] Meanwhile, regarding adverse reactions, this study observed no serious adverse reactions in patients treated with combination regimen, thereby demonstrating its potential clinical safety.…”
Section: Post-treatmentsupporting
confidence: 91%
“… 3 Another study demonstrated that the PPE and ovalbumin‐induced ACO model also develops allergic asthma. 4 Our overlap model used the previously reported A. alternata administration schedule. 2 This administration schedule increases the number of ILC2 and CD4 + T cells containing IL‐5 and ‐13 intracellularly in BAL fluid.…”
Section: Figurementioning
confidence: 99%
“…Correction: Evaluation of asthma-chronic obstructive pulmonary disease overlap using a mouse model of pulmonary disease Yong Suk Jo Following the publication of the original article [1], the authors identified an error in the author's name of Tai Joon An. The given name and family name were erroneously transposed.…”
Section: Open Accessmentioning
confidence: 99%
“…The incorrect author's name is: An Tai Joon The correct author's name is: Tai Joon An The author group has been updated above and the original article [1] has been corrected.…”
Section: Open Accessmentioning
confidence: 99%